Limitations to Understanding Scientific Concepts and Academic Performance in Primary Science among Primary Six Pupils in Cross River State Nigeria - U. Cornelius-Ukpepi, Bernedette; O. Enukoha, Obinna (International Journal of Evaluation and Research in Education (IJERE), 2013)
This study examined the relationship between limitations to understanding scientific concepts and academic performance in Primary Science among primary six pupils in Cross River State, Nigeria. In order to achieve the set objectives of this study, two hypotheses were formulated and tested.  Two instruments were used for data collection. They were limitations to understanding scientific concepts questionnaire (LUSCQ) and a 50-item primary science achievement test.  These instruments were validated and administered to 1818 pupils out of  68,201 pupils in 70 schools in the study population. A proportionate stratified random sampling technique was adopted hence; the study area was stratified into three educational zones with different populations. The data obtained were analyzed using Pearson Product Moment Correlation Coefficient (r) statistical tests at 0.05 level of significance.  The major finding of this study was that there was a significant relationship between limitations to understanding scientific concepts and academic performance in primary science.  Based on the findings, it was concluded that if pupils study scientific concepts adequately and  grasping the knowledge of technical terms in science and have adequate experience of science concepts,  it will help them to perform well in primary science.DOI: http://dx.doi.org/10.11591/ijere.v2i2.1716